APPLICATION OF THE WEIGHTED PRODUCT METHOD FOR THE SELECTION OF CANDIDATES FOR THE NATIONAL SCIENCE OLYMPIAD AT SMK YAPIM BIRU - BIRU - Dedi Candro Parulian Sinaga; Baringin Sianipar (INFOKUM, 2021)
The National Science Olympiad is a competition in the field of science for elementary, middle, and high school students in Indonesia. Students who take part in the National Science Olympiad are students who pass the selection at the district and provincial levels are the best students from their respective provisions. The implementation of OSN aims to find talent, learn to compete, increase insight and increase potential in the field of science which is carried out once a year. school is to choose students who fit the criteria as prospective participants who follow OSN appropriately, because the selection process is based on the best decision based on the level of ability and knowledge of students is not easy. Selecting students who take part in the Olympics will be carried out by the teacher / principal through a written test and the student's academic score, so it takes a long time because it selects students first.